Legal Protection for Public Accountants in Safeguarding Independence and Objectivity in Financial Statement Audits - M saleh; Suparnyo (CV. Norma Global, 2025)
Public accountants occupy a strategic position in safeguarding the integrity of financial statements, which constitute a critical foundation for economic decision-making by diverse stakeholders. In fulfilling their professional responsibilities, public accountants are expected to consistently uphold the principles of independence and objectivity. However, client pressure, conflicts of interest, and external interference frequently pose significant threats to auditor professionalism and ethical integrity. Accordingly, robust legal protections are essential to ensure that public accountants can perform their duties independently and objectively, free from coercion or undue influence that may compromise ethical standards. This paper seeks to examine the existing legal frameworks that provide protection for public accountants in Indonesia, encompassing statutory regulations, professional codes of ethics, and relevant jurisprudence. Employing a normative juridical research approach, the study emphasizes the critical role of regulatory strengthening and legal enforcement in promoting accountability and integrity within the public accounting profession. The findings indicate that, despite the presence of a legal framework governing the profession, gaps remain in its implementation and in providing substantive protection for auditor independence. In response, this paper offers strategic recommendations aimed at reinforcing legal safeguards and ethical standards within the practice of financial auditing.